Effect of changing antiretroviral treatment eligibility criteria on patient load in Kampala, Uganda - Konde-Lule, Joseph; Makumbi, Fred; Pakker, Nadine; Muyinda, Asad; Mubiru, Mesach; Cobelens, Frank G.J. (AIDS care, 2011)
In many resource-poor countries, CD4 count thresholds of eligibility for antiretroviral treatment (ART) were initially low (<200 cells/mm3) but are now being increased to improve patient survival and to reduce HIV transmission. There are few quantitative data on the effect of such increases on the demand for ART. The objective of this study was to measure HIV prevalence and the proportion of HIV-positives eligible for antiretroviral therapy at different CD4 cut-off levels among users of public health care services in Kampala, Uganda. We recruited 1200 adults from three primary care clinics in Kampala, including equal numbers of family planning (FP) clients, pregnant women, adult patients with any complaint, and persons seeking HIV counseling and testing. All participants were screened for HIV and those positive had a CD4 count done. HIV prevalence in all patients was 16.9% (203/1200). ART eligibility based on CD4 counts significantly increased from 36% at a 200 cells/mm3 cut-off to 44% at 250 cells and to 57% at 350 cells cut-off (p for χ2 trend<0.001). We concluded that changing cut-off levels to higher CD4 counts will significantly increase patient load in Kampala's primary care clinics, but a phased implementation should minimize negative effects on quality of care.
Keywords: Eligibility criteria; HIV antiretroviral therapy